Teksty narracyjne uczniów w świetle morfologii Władimira Proppa - Joanna Maria Garbula (Problemy Wczesnej Edukacji)
Children create narratives by imitating styles present in their culture and own experiences. Hence, nurseries and primary schools play an important role in children’s building narratives. My intention has been to present narratives constructed by children taking into consideration the form rather than the content, as it had been done by V. Propp in his morphology. This type of researching children’s texts has not been previously employed in early school pedagogy. The analyses demonstrated that most stories created by early school pupils assume the form of modified and updated fairy tales, with a different number of functions.